Visualidades em práticas pedagógicas: discutindo os processos de leitura e compreensão crítica de imagens na formação docente em Artes Visuais - Torres, Laura Sacco dos Anjos (2021)
This research seeks to discuss the aspects of visuality that are present in the discourses of Visual Arts teachers, who work with the final years of Elementary School in the city of Pelotas, by tracing the main tendencies that support their pedagogical practices. Data analysis is backed in a dialogical perspective of language from Bakhtin and the Circle (BAKHTIN, 2011; VOLOCHINÓV, 2018; SOBRAL, 2009), according to which the analyst looks at the linguistic marks of the statements in search of the meanings constructed in discourse related to the aspects of visuality, as well as of the understanding that Visual Arts teachers have about the concepts of image and visuality. The results of the research demonstrate a formalistic understanding of the concept of image, by most of the interviewees, with only one of the participants being familiar with the understanding of visuality, as a concept of visual culture. The interviewees' utterances are representative of a construction of knowledges, owned teachers, that become evident in their plurality and heterogeneity through the exercise of teaching (TARDIF, 2005). By analyzing the interviewees‘ utterances, it was verified that the teachers had a limited access to different perspectives and methodological approaches for reading, critical understanding and appreciation of images, during their initial training. It is believed that the contact with a diversity of perspectives can provide important resources for the construction of pedagogical knowledges, which can be mobilized in the teaching practice.